Activation of the olefinic C-H bond of NHC and NHO by perimidine-based silicon and germanium compounds - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Tothadi, Srinu; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2023)
In this manuscript, several backbonegermylene-functionalized zwitterioniccompounds were prepared conveniently from the corresponding N-heterocycliccarbenes or N-heterocyclic olefins in a single step through backboneC-H activation. Our initial motivation was to generate a silylenefrom C10H6(Me3SiN)(2)SiHCl(2) using ItBu [ItBu= (1,3-ditert-butyl)imidazol-2-ylidene], but instead, the reactionled to deprotonation from the imidazolium backbone of ItBu, forming the imidazolium salt with a silyl backbone at the C4position (3). We presumed that the reaction proceededthrough the generation of an ephemeral silylene. We subsequently preparedthe analogous germylene (4) and reacted it with IDipp[IDipp = 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidene], ItBu, and IDipp=CH2. Spectroscopic and crystallographicanalysis of these complexes revealed that, in all cases, there wasdeprotonation from the backbone and formation of zwitterionic products(5-7). When the hydrogen in the NHCbackbone was replaced with methyl groups such as IDipp(Me) (1,3-bis(2,6-diisopropylphenyl)-4,5-dimethylimidazol-2-ylidene),simple adduct formation occurred, exemplified by the isolation ofIDipp(Me)& BULL;Ge(NSiMe3)(2)C10H6 (8).

Unprecedented C-F bond cleavage in perfluoronaphthalene during cobaltocene reduction - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Sangole, Mayur; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Singh, Kirandeep; Sen, Sakya S. (DALTON TRANSACTIONS, 2024)

Germylene mediated reductive C-C and C-N coupling of an isocyanide and its device application - Gour, Kritika; Pramanik, Debjit; Dash, Soumya Ranjan; Shinde, Dipak Dattatray; Venugopal, Geethu; Vanka, Kumar; Rath, Arup K.; Sen, Sakya S. (Angewandte Chemie-International Edition, 2025)
We have demonstrated a unique reductive coupling of 4-iodophenyl isocyanide, facilitated by a perimidine-based N-heterocyclic germylene (NHGe), which yields a bis-spirogerma compound featuring simultaneous C-C and C-N bond formation. This reaction, which leads to the oxidation of germanium from +2 to +4, represents a significant departure from previously documented isocyanide-germylene interactions. The product exhibits extensive conjugation across its bicyclic C4Ge2N2 framework, conferring distinct photophysical properties, including prominent orange luminescence in both solution and solid states. The photophysical properties are supported by the TD-DFT calculations confirming an n ->pi* transition. The potential application of this compound in optoelectronic devices, particularly as a hole transport layer in PbS quantum dot solar cells, is also explored, with promising preliminary results.
Keywords: Germylene; hole transport layer; Isocyanide; reductive coupling

Kekule diradicaloid with a naphthalene spacer - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2026)
The availability of a diverse array of carbenes led to the generation of a catalog of carbene based Kekule diradicaloids, but the linker in such molecules is mostly limited to phenylene or biphenylene. Here we have prepared a closed-shell Kekule diradicaloid (2) separated by a naphthalene moiety and stabilized by two capping 5-SIDipp [5-SIDipp = 1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] from the reduction of the corresponding dication (1). The combined experimental and computational studies confirm that 2 is in a closed-shell singlet state exhibiting a singlet-triplet energy difference (Delta ES-T) of 18.7 kcal/mol, which is considerably lower than Thiele's version (29.1 kcal/mol).